Tantangan dan Solusi bagi Pekerja Disabilitas di Tempat Kerja Modern - Khusi Nadiratul Laili; Firdaus Firmansyah; Meylisa Eka Hidayah; Willy Wicaksono Wibowo (SS&H: Studies in Social Sciences and Humanities, 2024)
The integration of disabled individuals into the workforce remains a significant challenge despite existing legal frameworks promoting inclusivity. This study explores the barriers faced by disabled workers, including workplace discrimination, limited accessibility, and lack of career advancement opportunities. Through a literature review approach, the research highlights the importance of inclusive policies, specialized training programs, assistive technologies, and the role of governments in ensuring fair employment practices. Findings suggest that although legal protections exist, enforcement remains weak, leading to persistent workplace inequalities. Companies must adopt inclusive strategies, such as workplace accommodations and flexible policies, to enhance productivity and ensure equal opportunities. Moreover, public awareness campaigns are crucial to changing societal perceptions and eliminating stereotypes against disabled workers. Strengthening regulatory compliance, increasing government incentives for inclusive hiring, and providing tailored skills development programs can further enhance employment opportunities for disabled individuals. The study concludes that a multi-stakeholder approach is essential to creating an equitable and accessible work environment for all.